Thermoforming of Non-Developable Surfaces: Challenges in the Manufacture of Solid Surfaces, the Case of Krion K-Life - Ferran Ventura Blanch; Vishal Shahdadpuri Aswani; Pablo Hernández Vílchez (Applied Sciences)
This research arises from the need to rethink children’s play spaces found in the city through new manufacturing methods of solid surface materials such as Krion K-Life 1100, which allow the creation of complex ergonomic shapes. The method consisted of an iterative digital fabrication process, in which a series of molds were developed and adjusted to thermoform a solid surface material, adapting the design in each iteration according to the results obtained. Parametric digital modeling techniques and in-depth curvature analysis were carried out to optimize the geometry, in order to meet the technical limitations of the material and the manufacturing process itself. The results showed that, through precise adjustments in the curvature and thickness of the surface, it is possible to thermoform the solid surface without defects, such as folds or wrinkles, revealing it as a viable material for the generation of complex double-curved geometries, opening up a range of possibilities from the creation of new children’s spaces to parametric facades optimized according to their location.